OPTIMIZATION OF THE ELECTRO-ACOUSTIC SPUTTERING PROCESS BY THE MICROHARDNESS CRITERION - D.N. MALEYEV; W.H. AL-TIBBI; D.A. CHILIKIN (Advanced Engineering Research)
Influence of acoustic parameters (amplitude of ultrasonic oscillations A (mcm), frequency of ultrasonic oscillations (Khz), and a corner between the axis of the wave guide and the vector direction of longitudinal-twisting oscillations (degrees)) process of an electroacoustic dusting of the protective coatings on quality of coating (micro hardness) is investigated. On the basis of the executed research the mathematical model of dependence of micro hardness of a coating from acoustic parameters of process is developed and adequacy of the received model is checked.